Two chromosomal reference genome sequences for the malaria mosquito, Anopheles (Nyssorhynchus) darlingi, Root, 1926 from French Guiana and Peru [version 1; peer review: 3 approved] - Carlos Tong; Joseph M Vinetz; Harriet F Johnson; Jan E Conn; Mara K N Lawniczak; Sarah E Pelan; Marcela Uliano-Silva; Martin G Wagah; Daniel E Neafsey; Jonathan M D Wood; Damon-Lee B Pointon; James W Torrance; et al. (Wellcome Open Research)
We present two genome assemblies, each generated from individual female Anopheles (Nyssorhynchus) darlingi (the malaria mosquito; Arthropoda; Insecta; Diptera; Culicidae), from wild populations in French Guiana and Peru. The genome sequences are approximately 180 megabases in span. The majority of each assembly is scaffolded into three chromosomal pseudomolecules with the X sex chromosome assembled. The complete mitochondrial genomes were also assembled and are both 15.4 kilobases in length. The assemblies differ by two inversions in chromosome arm 2R.